Features of vitality and adaptability of students in crisis situations - Kordunova , Natalia; Mudrak , Igor; Dmytriiuk, Natalia (Psychological Prospects Journal, 2021)
Purpose. The article provides a theoretical analysis of the psychological features of vitality and adaptability of students in crisis situations. Methods. To realize the purpose of the study, the following methods of theoretical scientific research were used: analysis, synthesis, generalization. To conduct an empirical study — «Test of viability» S. Maddi (adaptation of D. Leontiev, O. Rasskazova), questionnaire «Adaptability» A.G. Maklakova, С.В. Chermyanin. The study involved 80 first-year students of Volyn Lesya Ukrainka National University. Results. The analysis of Ukrainian and foreign works allows us to state that vitality is a necessary element of the adaptive potential of the individual; allows a person to resist the negative effects of the environment, provides confidence and determination in their own actions, helps to maintain health and maintain optimal levels of efficiency and activity in crisis situations. Conclusions. In general, we can conclude that life is an important component of student adaptability in crisis situations. It is proved that adaptability as a stable property of the individual is the internal basis of the ability to adapt to any living conditions and willingness to interact with the environment. The prospects for further research are seen in the study of psychological features in their relationship with other personality traits that will contribute to more effective functioning of the individual in the changing conditions of today.